Advancing orebody knowledge for cave mining using high-resolution rock strength measurements - Can Cetin, M.; Nadolski, S.; Fung, Y.; Byambadorj, N.; Shijir, A. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Cave mining projects rely on an accurate understanding of rock mass strength and variability to inform cave design, draw strategy and geotechnical risk management. However, conventional geotechnical testing is typically limited by cost, sample availability and testing throughput, which restricts the spatial resolution of data available for cave mining applications. The Minpraxis Tester (MPT) is a compression-breakage test device that continuously treats half-core samples along their length while operating within a conventional assay preparation workflow. By extracting strength, hardness and density information during sample preparation, the MPT enables geotechnical and geometallurgical characterisation of resource core that would otherwise not be tested using industry-standard methods. This approach substantially increases the volume and resolution of measured data, capturing variability at the centimetre scale along core intervals. The MPT generates continuous estimates of rock strength and hardness parameters, including point load index (IS50) and drop weight index, while preserving the ability to process samples for assay. In addition, the device can test irregular lump samples, allowing strength estimates to be derived from broken core pieces and remnants from other laboratory tests that would normally lack valid measurements. This paper presents an ongoing validation study using drill core samples from the Oyu Tolgoi mine. MPT measurements were conducted on selected core intervals, with conventional geotechnical testing performed on neighbouring material to provide reference datasets. The work focuses on evaluating how high-resolution, continuous strength measurements can support cave mine design and geotechnical modelling. The results demonstrate the potential for significantly increasing data density for cave mining projects, as well as other mining methods, and highlight how continuous strength characterisation may support improved orebody knowledge, geotechnical block modelling and more-informed cave design decisions.